Low Light Amplification Threshold and Reduced Efficiency Roll‐Off in Thick Emissive Layer OLEDs from a Diketopyrrolopyrrole Derivative. Issue 16 (11th April 2022) - Shukla, Atul; Entoma, Volter; McGregor, Sarah K. M.; Hasan, Monirul; Mamada, Masashi; Moore, Evan G.; Adachi, Chihaya; Lo, Shih‐Chun; Namdas, Ebinazar B.
Abstract: External quantum efficiency (EQE) roll‐off under high current injection has been one of the major limiting factors toward the development of organic semiconductor laser diodes (OSLDs). While significant progress in this regard has been made on organic semiconductors (OSCs) emitting in the blue–green region of the visible spectrum, OSCs with longer wavelength emission (>600 nm) have fallen behind in both material development and the advancement in device architectures suitable for the realization of OSLDs. Therefore, to make simultaneous incremental advancements, a host–guest system comprising of a high performing poly(9, 9‐dioctylfluorene‐ alt ‐benzothiadiazole) (F8BT) polymer and an efficient small molecule laser dye, dithiophenyl diketopyrrolopyrrole (DT‐DPP), is used. This combination provides an extremely low amplified spontaneous emission threshold of 4.2 µJ cm −2 at an emission wavelength of 620 nm. The solution‐processed organic light‐emitting diodes (OLEDs) fabricated using this system exhibit a high external quantum efficiency (EQE) of 2.6% with low efficiency roll‐off and high current injection up to 90 A cm −2 to yield ultrahigh luminance of over 1.5 million cd m −2 . Abstract : A new strategy to demonstrate simultaneous advancement in light amplification and electroluminescent characteristics of a red‐emitting organic laser dye, DT‐DPP, is successfully utilized. The strategy amalgamates the best of both the host and the guest material efficiently into one system and provides an important advancement for the future development of organic injection laser.